Nocardia infection of the mastoid in an immunocompromised patient. - Subha, Sethu Thakachy; Raman, Rajagopalan (Malaysian Medical Association., 2004)
A rare case of Nocardia infection of mastoid is presented in an immunocompromised patient.Nocardia species are opportunistic pathogens found in immuno compromised patients. Acute suppurative otitis media caused by this microorganism have been reported but however no report of mastoiditis was found in the English literature. We report a rare case of mastoiditis with petrous apex abscess caused by Nocardia in a HIV infected patient.